Radiologic Science Students’ Perceptions of Parental Involvement. - DuBose, Cheryl; Barymon, Deanna; Vanderford, Virginia; Hensley, Chad; Shaver, Gary (Radiologic Technology)
Background A new generation of students is in the classroom, and they are not always alone. Helicopter parents, those who hover around the student and attempt to ease life’s challenges, are accompanying the students to radiologic science programs across the nation. Purpose To determine radiologic science students’ perception regarding their parents’ level of involvement in their lives. Methods A survey focused on student perceptions of parental involvement inside and outside of the academic setting was completed by 121 radiologic science students at 4 institutional settings. Results The analysis demonstrates statistically significant relationships between student sex, age, marital status, and perceived level of parental involvement. In addition, as financial support increases, students’ perception of the level of parental involvement also increases. Discussion Radiologic science students want their parents to be involved in their higher education decisions. Research indicates that students with involved parents are more successful, and faculty should be prepared for increased parental involvement in the future. Conclusion Radiologic science students perceive their parents to be involved in their academic careers. Ninety-five percent of respondents believe that the financial support of their parent or parents contributes to their academic success. Sixty-five percent of participants are content with their parents’ current level of involvement, while 11% wish their parents were more involved in their academic careers.